Notes on the experimental laboratory and field culture of Lessonia variegata (Laminariales) - Kate Neill; Sheryl Miller; Wendy Nelson (New Zealand Journal of Marine and Freshwater Research, 2025)
The kelp Lessonia variegata J. Agardh (Lessoniaceae) is a potential aquaculture target for bioactive compounds. We investigated the control and management of Lessonia gametogenesis, the settlement and retention of sporophytes on various culture strings, and the upscaling of string settlement for field trials. In the laboratory we held gametophytes at low light conditions for 2.5 months before altering conditions to stimulate them into the next part of the life cycle. Settlement and development of sporophytes was highest on Korean culture string, followed by Builders Line, however after agitation, fewer sporophytes were dislodged from the Builders Line. Larger scale settlement of spores onto 15 m lengths of Builders Line was successful, with sporophytes reaching ∼5 mm length in 46 days. Eight weeks after out‐planting, the sporophytes were heavily fouled with other algae. Although the results presented here were small‐scale and lack replication, they add to the existing knowledge on the biology and cultivation of this species.